Measurement and prediction of the physical properties of an aqueous sodium salt of L-phenylalanine - Garg, S. (Serbian Chemical Society, 2017)
Physical properties, such as density, refractive index and viscosity, of an aqueous sodium salt of (S)-2-amino-3-phenylpropionic acid (L-phenylalanine, Na-Phe) were investigated in this work. These properties were measured over a temperature range of 298.15-343.15 K at atmospheric pressure. The mass fractions (w) of Na-Phe were 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35 and 0.40. The analysis of the experimental data showed that the values of density, refractive index and viscosity decreased with increasing temperature at any constant concentration of Na-Phe. However, these values increased with increasing concentration at any constant temperature. The density values were used to estimate the thermal expansion coefficient. The thermal expansion coefficient increased slightly with increasing temperature and concentration. The density and refractive index data were correlated using a modified Graber equation, while, the viscosity data were correlated using a modified Vogel- -Tamman-Fulcher (VTF) equation. In all the cases, quantitative analyses of the influence of temperature and concentration were performed.